Reply to ‘Thomson scattering in inhomogeneous plasmas: The Role of the Fluctuation-Dissipation Theorem’ - Kozlowski, PM; Gericke, DO; Regan, SP; Gregori, G (Nature Publishing Group, 2018)
In a comment on our article “Theory of Thomson scattering in inhomogeneous media”, V. V. Belyi asserts that there is an inconsistency in our method of applying gradient effects via the dielectric superposition principle, in violation of the fluctuation-dissipation theorem; and that his Klimontovich-Langevin formulation would be more appropriate to our application. While we agree that a generalization, along the lines of Belyi’s work, would be required for strongly coupled systems, for the weakly coupled systems which we considered, these corrections are not necessary and our approach is still appropriate.